Alexander’s Settlement of the Upper Satrapies in Policy and Practice - Lerner, Jeffrey D. (Anabasis. Studia Classica et Orientalia, 2018)
The paper examines the policy of urbanism in Central Asia as it was enacted by Alexander the Great during his anabsis in the region, as it is presented by ancient Greek and Latin authors. The analysis is two-fold: a concise historical reconstruction of the campaign, followed by the settlement policy as it was enacted. The most important conclusion raised by the investigation is that the majority of foundations attributed to Alexander were in fact little more than fortresses and garrisons in cities, or cities renamed for him, while the real work of establishing a policy of urbanism was left to his successors.